The impact of historical corporate irresponsibility on environmental, social and governance compliance in the EU - Chmelíková, Gabriela; Chládková, Helena; Kučerová, Renata; Špička, Jindřich (Nature Publishing Group, 2026)
This study examines whether historical corporate social irresponsibility is associated with later compliance with environmental, social and governance principles among European business populations. Using data from RepRisk for the period 2015-2020, we analyse environmental, social and governance incidents reported for firms in European Union countries and aggregate the information at the country-year level. We operationalise corporate misconduct with two complementary measures. First, we measure the prevalence of environmental, social and governance incidents, defined as the share of firms with at least one environmental, social and governance incident in a given country and year. Second, we measure the intensity of environmental, social and governance incidents, defined as the average RepRisk, reputational risk indicator, among firms involved in incidents in a given country and year. We test whether past intensity is associated with subsequent prevalence using panel regression models with macroeconomic controls. The results show a statistically significant negative relationship between lagged intensity and current prevalence, suggesting that more severe past shocks are followed by a lower share of incident-involved firms at the country level. Interpreted through institutional theory and path dependency, the findings indicate that scandals may function as institutional signals that contribute to shifts in acceptable business practices beyond the firms directly involved. This study provides implications for policy by emphasising the role of transparent monitoring, consistent reporting standards, and stakeholder oversight in supporting sustainable corporate conduct.
Keywords: Corporate Social Irresponsibility; ESG incidents; Reputational risk; Institutional theory; Path dependency